2021
DOI: 10.1016/j.heliyon.2021.e07082
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the association between mental health and subjective sleep quality during the COVID-19 pandemic among Bangladeshi university students

Abstract: The outbreak of new coronavirus disease has triggered a global panic, affecting the mental well-being of people of all ages, including students. The aim of this study was to explore the relationship between selfreported mental health concerns and subjective sleep quality of the Bangladeshi university students during the COVID-19 pandemic. A web-based cross-sectional study was conducted to maintain the social distancing recommended by the World Health Organization. There were 1,317 student responses from 49 un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 47 publications
6
39
1
6
Order By: Relevance
“…Findings indicate that 36.6% of students had poor sleep quality, while 40.5% experienced psychological distress. Comparable with our results, a recent study in Bangladesh reported that University students were mentally distressed and experiencing poor subjective sleep quality during the pandemic (58). Similar results were also revealed by Martinez-Lezaun et al (59), who reported 70.7% of the University students showed worse sleep quality during the lockdown.…”
Section: Discussionsupporting
confidence: 91%
“…Findings indicate that 36.6% of students had poor sleep quality, while 40.5% experienced psychological distress. Comparable with our results, a recent study in Bangladesh reported that University students were mentally distressed and experiencing poor subjective sleep quality during the pandemic (58). Similar results were also revealed by Martinez-Lezaun et al (59), who reported 70.7% of the University students showed worse sleep quality during the lockdown.…”
Section: Discussionsupporting
confidence: 91%
“…This may lead to differences in fear of COVID-19 levels of different cultures (allocentric vs. egocentric). Overall, the average age of the sample, female proportion, and culture were considered moderators in the study as these variables were treated as moderators in individual studies (e.g., Ahammed et al, 2021; Kassim et al, 2021; Midorikawa et al, 2021; Siddique et al, 2021; Tsipropoulou et al, 2020).…”
Section: Fear Of Covid-19 and Mental Healthmentioning
confidence: 99%
“…Consequently, this study aimed to investigate the prevalence of poor sleep quality by using the PSQI and its associated factors among Bangladeshi people during the COVID-19 pandemic. However, some studies on sleep disturbance, subjective sleep quality, and insomnia have recently been published, conducted with different groups in Bangladesh (45)(46)(47)(48). Though one of these studies assessed the sleep quality by using the PSQI among Bangladeshi general people with limited samples, it did not investigate any COVID-19 pandemicrelated factors and their relations with poor sleep quality (48).…”
Section: Introductionmentioning
confidence: 99%